Karyotype Patterns of Hypsolebias antenori (Cyprinodontiformes: Rivulidae): An Endangered Killifish of the Semiarid Region of Brazil - Wallace Silva do Nascimento; Juliana Galvão Bezerra; Paulo Augusto Lima-Filho; Maria Emília Yamamoto; Sathyabama Chellappa; Wagner Franco Molina (The Scientific World Journal)
Annual fish which belong to the order Cyprinodontiformes constitute an excellent model for evolutionary studies. their short life cycle, distribution in ecologically dynamic environments, and low agility make them favorable for genetic analyses. The species Hypsolebias antenori (Rivulidae), encountered in seasonal pools located in the semiarid region of Northeastern Brazil, has been the object of surveys with a view to study its ecological and behavioral aspects. This study reports on the karyotype patterns of this species, which represents the first contribution to the cytogenetics of this genus. The karyotype of this species is composed of 2n = 48 chromosomes (6m + 4sm + 36st; NF = 96); the heterochromatic regions are located in centromeric or pericentromeric position and are more pronounced in the nucleolar organizer regions. Two sites Ag-NORs/CMA+/DAPI were identified in the short arms of pairs 2 (metacentric) and 21 (subtelocentric). Unlike the other species of this family which show an evolution modulated by events of centric fusions, H. antenori shows the maintenance of a basal diploid number and the large number of bibrachial elements indicates karyotypic diversification derived by pericentric inversions. Cytogenetic analyzes in this species will provide new taxonomic markers capable of being utilized in conservation issues and systematics.